GAMBARAN STATUS GIZI DAN INFEKSI SALURAN PERNAFASAN AKUT (ISPA) PADA ANAK BALITA KELUARGA PEROKOK DI DESA PADANG BULAN KECAMATAN KOTANOPAN KABUPATEN MANDAILING NATAL TAHUN 2015 - Siti Khadijah Nasution; Etti Sudaryati; Ernawati Nasution (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
Smoking is one of the unhealthy behaviour that can be harmfull and very disturbing of ourself and others around us especially for those who vulnarable groups such as children under five years. Exposure to ciggarete’s smoke affect occurance of ISPA, there where children under five who exposure cigarete’s  smoke take a high risk than unexposure cigarete’s smoke. Children under five years who got suffering Infectious disease could affected intake nutritional cannot absorbed body well so the nutritional status decreased. The aim of this research to describe nutritional status and ISPA on those household as smoker family in Desa Padang Kecamatan Kotanopan. The type of this research is descriptive with cross setional design. Total sample are 40 childeren under five years who taken from smoker family. Data was collected by interviews and questionnaires. The result showed that, nutritional status based on weight for age children under five years in Desa Padang Bulan Kecamatana Kotanopan there are (70%)  good nutrition and (30%)  malnutrition. Nutritional status based on height for age there are (82,5%) good nutrition and (17,5%) malnutrition. Nutritional status based on weight for age there are (75%) good nutritioan and (22,5%) thin. The conlusion of this research was the higher consumption smoking’s family and increasingly frequent expose of ciggarete smoke children under five years so could affected of nutrional status and ISPA of children under five years. It is Expecting of this research to parent’s children under five years are decrease to consume of cigarete and do not smoking in the house so as reduce exposure among children under five years. Keywords : Nutritional status, ISPA, Family’s Smoker, Children Under Five Years.